Bilateral Asymmetry in Ocular Counter-Rolling Reflex Is Associated With Individual Motion Sickness Susceptibility - Sugawara, Tomoko; Wada, Yoshiro; Ito, Taeko; Sakai, Hiroyuki (Frontiers in Neurology, 2021)
Accumulating evidence suggests that individual variations in vestibular functions are associated with motion sickness (MS) susceptibility. We investigated whether vestibular functions in the reflex and cortical pathways could predict individuals' susceptiblility to MS. MS-susceptible and control adults were recruited according to the Motion Sickness Susceptibility Questionnaire score. Otolith reflex and cortical functions were assessed using the ocular counter rolling test and the head-tilt subjective visual vertical test, respectively. Moreover, canal reflex functions were assessed using the video head-impulse test. Bilateral asymmetry of each function was compared between the MS-susceptible and the control groups. Although the two tests for otolith functions were conducted using the same stimulation (lateral head tilt), bilateral asymmetry of otolith reflex rather than cortical function was associated with MS susceptibility. Contrastingly, bilateral asymmetry of canal reflex function was not significantly associated with MS susceptibility. Our data suggests that bilateral asymmetry in the otolith reflex pathway is capable of predicting individuals' susceptiblity to MS. However, our data also suggest that the association between vestibular function and MS susceptibility can vary based on the vehicle types. Future vehicles, such as self-driving cars, will make us aware of other vestibular function associated with MS susceptibility.